Respuesta :
Answer:
The answer to your question is the first option
Step-by-step explanation:
Data
C ( -3, -1)
P (1, 2)
Process
1.- Calculate the radius
r = [tex]\sqrt{(2 + 1)^{2} + (1 + 3)^{2}}[/tex]
r = [tex]\sqrt{3^{2} + 4^{2}}[/tex]
r = [tex]\sqrt{9 + 16}[/tex]
r = [tex]\sqrt{25}[/tex]
r = 5
2.- Substitute the center and the radius in the equation of the circle. Remember to change the signs of the center.
Equation
(x - h)² + (y - k)² = r²
Substitution
(x + 3)² + (y + 1)² = 5²
(x + 3)² + (y + 1)² = 25